Energy partitioning in cattle fed diets based on tropical forage with the inclusion of antibiotic additives. - Marcelina Pereira da Fonseca (PLoS ONE, 2019)
The aim of this study was to describe energy partitioning in dairy crossbreed bulls fed tropical forage-based diets supplemented with different additives. Twenty F1 crossbred bulls (Holstein x Gyr) with initial and final live weight (LW) averages of 190 ± 17 and 275 ± 20 kg were fed sorghum (Sorghum bicolour) and Tanzania grass (Panicum maximum cv. Tanzania) silage (70:30 DM basis) with supplemented concentrate at a forage to concentrate ratio of 50:50. The bulls were allocated to four treatment: control groups (without additives), monensin [22 mg/kg monensin dry matter (DM)] (M), virginiamycin (30 mg/kg virginiamycin DM) (V), and combination (22 mg/kg DM of monensin and 30 mg/kg DM of virginiamycin) (MV), in a completely randomised design. The intake of gross energy (GE, MJ/d), digestible energy (DE, MJ/d), metabolizable energy (ME, MJ/d), as well as energy losses in the form of faeces, urine, methane, heat production (HE), and retained energy (RE) were measured. Faecal output was measured in apparent digestibility trial. Right after the apparent digestibility trial, urine samples were collected in order to estimate the daily urinary production of the animals. Heat and methane production were measured in an open circuit respirometry chamber. The intake of GE, DE, and ME of the animals receiving monensin and virginiamycin alone or in combination (MV) showed no differences (P>0.05) from the control treatment. However, the MV treatment reduced (P<0.05) the methane production (5.44 MJ/d) compared to the control group (7.33 MJ/d), expressed in MJ per day, but not when expressed related to gross energy intake (GEI) (CH4, % GEI) (P = 0.34). Virginiamycin and monensin alone or in combination did not change (P>0.05) the utilization efficiency of ME for weight gain, RE and net gain energy. This study showed that for cattle fed tropical forages, the combination of virginiamycin and monensin as feed additives affected their energy metabolism by a reduction in the energy lost as methane.